Activin and follistatin in female reproduction. - Muttukrishna, S; Tannetta, D; Groome, N; Sargent, I (2004)
Activin and follistatin were initially identified in the follicular fluid based on their effects on pituitary FSH secretion in the mid-1980s. It is now evident that activin, follistatin and activin receptors are widely expressed in many tissues where they function as autocrine/paracrine regulators of a variety of physiological processes including reproduction. The major function of follistatin is to bind to activin with high affinity and block activin binding to its receptors. Total activin A and follistatin are also found in the maternal circulation throughout pregnancy. Activin A levels are increased in abnormal pregnancies such as pre-eclampsia, fetal growth restriction and gestational hypertension. The placenta, vascular endothelial cells and activated peripheral mononuclear cells (PBMC) may all contribute to the raised levels of activin A in pre-eclampsia with unaltered follistatin in pre-eclamptic placenta, PBMCs or vascular endothelial cells suggesting the availability of 'free' activin A that could be biologically active in these cells.